STRATEGI PENYELENGGARAAN PROGRAM PENDIDIKAN PROFESI PENYULUHAN PERTANIAN DI STPP BOGOR - Yoyon Haryanto; Soesilo Wibowo; Lukman Effendy (Politeknik Pembangunan Pertanian Bogor, 2020)
Professional certification of agricultural extension workers than can be done through assessment. Competency assessment test can also be carried out through the professional education program. Professional education for agricultural extension officers was possible organized by STPP remember three things: (a) STPP is a college official, who can organize professional education in accordance with law number 20 of 2003 on national education system; (b) Agricultural extension college as the government regulation number 14 of 2010 can be transferred as a extension college official with professional education program after the Bachelor program or Diploma; and (c) Profession agricultural extension, made possible after the issuance of law number 16 of 2006 on agricultural extension system fisheries and forestry. The research goal is to identify the weaknesses, strengths, opportunities and challenges faced in the implementation of STPP and professional education counseling and determine appropriate strategies in agricultural extension education profession by STPP. This study used SWOT analysis approach. Number of samples for alumni and policy makers in the area as many as 152 people and 17 persons from the faculty so that the total number of respondents was 169 people. Based on the results of this research is that the operational activities that will be implemented should optimally utilize the entire power of the STPP and transformation process to achieve a distinctive competence and operational objectives STPP. A very useful indicator ideate operational strategy are: (a) Commitment to existing activities within the scope of STPP; (b) Conditions STPP current and planned ; (c) Transformation of the activities of the organization that is able to transform inputs into value-added output; and (d) Distinctive competence is owned STPP specific capabilities to generate added value through a transformational process and support the overall goals of STPP. Conclusion This is a strategy for organizing fieldwork education Professional Studies Program Strategy Agricultural Extension is SO (StrengthOpportunities).